2021
DOI: 10.1016/j.celrep.2021.109886
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbiota affects the efficacy and prognosis of radiotherapy for colorectal cancer in mouse models

Abstract: Highlights d Colorectal cancer (CRC) progression is affected by oral microbiota d Oral microbiota alterations affect efficacy of radiotherapy and prognosis in CRC d Changes in oral microbiome tune bacterial pattern at CRC site but not peritumor d Oral F. nucleatum migrates to CRC sites, impairing radiotherapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…Moreover, it can migrate to the CRC locus, impair the therapeutic efficacy of radiotherapy, and affect patient prognosis. The use of metronidazole to kill F. nucleatum can reduce CRC radiotherapy resistance induced by oral microbiota (Dong et al, 2021). To enhance the chemotherapy effect of CRC, Zheng et al (2019) linked the F. nucleatum-specific phage with dextran nanoparticles loaded with CRC chemotherapeutic drugs form phage-guided nanoparticles, which can effectively inhibit the growth of F. nucleatum, significantly prolong the survival time of CRC mice and reduce the number of adenomas in Apc mice prone to intestinal adenomas.…”
Section: Crcmentioning
confidence: 99%
“…Moreover, it can migrate to the CRC locus, impair the therapeutic efficacy of radiotherapy, and affect patient prognosis. The use of metronidazole to kill F. nucleatum can reduce CRC radiotherapy resistance induced by oral microbiota (Dong et al, 2021). To enhance the chemotherapy effect of CRC, Zheng et al (2019) linked the F. nucleatum-specific phage with dextran nanoparticles loaded with CRC chemotherapeutic drugs form phage-guided nanoparticles, which can effectively inhibit the growth of F. nucleatum, significantly prolong the survival time of CRC mice and reduce the number of adenomas in Apc mice prone to intestinal adenomas.…”
Section: Crcmentioning
confidence: 99%
“…In parallel, oral Th17 cells induced by oral pathobiont expansion migrate to the gut and promote colitis, constituting both microbial and immunological pathways that link oral and gut health. Furthermore, Dong et al showed that the alterations of the oral microbiota, especially F. nucleatum colonization in CRC locus, can change the gut bacterial composition within tumours and influence the therapeutic efficacy and prognosis of radiotherapy for primary rectal cancer and CRC liver metastases in mouse models [ 125 ]. Kartal et al applied shotgun metagenomic and 16S rRNA sequencing to faecal and saliva samples from pancreatic ductal adenocarcinoma (PDAC) to identify diagnostic classifiers [ 96 ].…”
Section: Oral Pathogens and Systemic Diseasesmentioning
confidence: 99%
“…Dong and colleagues showed that F. nucleatum migrates from the oral cavity to the intestine, where it harbours within colorectal cancers and promotes radioresistance. Given the accumulated evidence pointing towards a role of F. nucleatum in modulating inflammation and driving HN-SCC, these results may offer new avenues of research [104].…”
Section: Efficacy Studiesmentioning
confidence: 88%